Generation of an RBM20-mutation-associated left-ventricular non-compaction cardiomyopathy iPSC line (UMGi255-A) into a DCM genetic background to investigate monogenetic cardiomyopathies - Eberle, Hanna; Rebs, Sabine; Hoppe, Stefanie; Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Meder, Benjamin; Streckfuss-Bömeke, Katrin (Stem cell research, 2024)
RBM20 mutations account for 3 % of genetic cardiomypathies and manifest with high penetrance and arrhythmogenic effects. Numerous mutations in the conserved RS domain have been described as causing dilated cardiomyopathy (DCM), whereas a particular mutation (p.R634L) drives development of a different cardiac phenotype: left-ventricular non-compaction cardiomyopathy. We generated a mutation-induced pluripotent stem cell (iPSC) line in which the RBM20-LVNC mutation p.R634L was introduced into a DCM patient line with rescued RBM20-p.R634W mutation. These DCM-634L-iPSC can be differentiated into functional cardiomyocytes to test whether this RBM20 mutation induces development of the LVNC phenotype within the genetic context of a DCM patient.
Online verfügbar: 16. Dezember 2023, Artikelversion: 22. Dezember 2023
Gesehen am 12.03.2024